Analisis Kontribusi Dan Efektivitas Penerimaan Pajak Daerah Sebagai Sumber Pendapatan Asli Daerah (PAD) Kota Bitung - Pirade Wenur, Gebriany (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
Local Own Revenue is all income that is locally obtained by the region and is collected based on the applicable laws and regulations. Regional Original Revenue (PAD) comes from regional taxes, regional levies, results of separated regional wealth management and other legitimate PAD. Regional taxes are taxes that are collected and managed by local governments and are used to finance regional development. Local taxes are a component that has the potential to increase local revenue (PAD). This study aims to find out how much the level of local tax contribution as a source of PAD and to find out how the level of effectiveness of local taxes in Bitung City. The research was conducted at the Regional Tax and Levies Management Agency. The analytical method used in this research is descriptive method. The results showed that the contribution of local taxes as a source of PAD for Bitung City during the 2014-2018 period was in the good category with an average contribution of 48.03% per year. The biggest contribution comes from the street lighting tax and the lowest contribution comes from the swallow's nest tax. The effectiveness of local taxes during the 2014-2018 period is included in the very effective category with a percentage of more than 100% each year.